2014
DOI: 10.1007/s10967-014-3686-9
|View full text |Cite
|
Sign up to set email alerts
|

Migration behavior of 134Cs and 137Cs in the Niida River water in Fukushima Prefecture, Japan during 2011–2012

Abstract: Total radioactivity of 137 Cs in water samples from the Niida River was 0.025-4.18 Bq/L during May 2011-November 2012. Higher radioactivity was found during May-September 2011 and after a high flow condition caused by a rain event in 2012. The particulate phase of 134 Cs and 137 Cs was 47-48 % for May-September 2011, 75-93 % in normal flow conditions and 86-91 % in high flow conditions after December 2011. These results indicate that the supply of 134 Cs and 137 Cs from the watershed differs from the early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…For example, in the Niida catchment, Nagao et al (2014) reported that the particulate fraction averaged 47% between May and September 2011 compared to 84% between December 2011 and November 2012. The differences were attributed to rainfall and declining availability of leachable sources of radiocesium that were likely washed off in greater concentrations early after the accident.…”
Section: Radiocesium Distribution Coefficient (Dissolved/particulate)mentioning
confidence: 99%
“…For example, in the Niida catchment, Nagao et al (2014) reported that the particulate fraction averaged 47% between May and September 2011 compared to 84% between December 2011 and November 2012. The differences were attributed to rainfall and declining availability of leachable sources of radiocesium that were likely washed off in greater concentrations early after the accident.…”
Section: Radiocesium Distribution Coefficient (Dissolved/particulate)mentioning
confidence: 99%
“…In addition, the lower 137 Cs concentration in the sediment layers above 18 cm suggests a decrease in the level of radioactivity in the Abukuma River catchment area, which can possibly be attributed to erosion of surface soil having a high radiocesium concentration . Indeed, monitoring of radiocesium in the Abukuma River and the Niida River indicates that the concentration of particulate and dissolved fractions in river water decreased markedly within 2011 at Fukushima (Nagao et al, 2015;Sakaguchi et al, 2015). In our recent work, we reported that the 137 Cs concentration was 140 and 350 Bq/kg in surface 5 cm sediments collected at the Kuroiwa site on September 16 and November 26, 2012, respectively ).…”
Section: Depth Distribution Of Radiocesium In the Bulk Sedimentsmentioning
confidence: 84%
“…Since the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident in March 2011, many researchers have acquired knowledge on the distribution of radionuclides, and particularly radiocesium ( 134 Cs and 137 Cs), in the environment, covering aerosols, soils, sediments, forests, rivers, and the Pacific Ocean (e.g., Kaneyasu et al, 2012;Kato et al, 2012;Kozai et al, 2012;Ohno et al, 2012;Tanaka et al, 2012Tanaka et al, , 2013aTanaka et al, ,b,c, 2014Tanaka et al, , 2015Adachi et al, 2013;Matsunaga et al, 2013;Kumamoto et al, 2014;Kanasashi et al, 2015;Nagao et al, 2015;Nagakawa et al, 2015;Sakaguchi et al, 2015). Most of the radiocesium deposited on the surface of the land remained within a depth of 5 cm from the surface (Kato et al, 2012;Tanaka et al, 2012;Ohno et al, 2012;Matsunaga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Niida River system in northeastern Fukushima Prefecture has a 78-km-long watershed with an area of 585 km 2 [5]. The upper watershed is located 30-40 km northwest of the FDNPP and is affected by relatively high levels of radioactive contamination, with 137 Cs inventory of >300 kBq m 2 ( Fig.…”
Section: Methodsmentioning
confidence: 99%